Comprehensive right heart systolic function assessment using cardiac magnetic resonance imaging after inferior ST elevation myocardial infarction - Nor Hanim, Mohd Amin; Asri, Said; Seng, Keong Chua; Chi, Yen Voon; Ning, Zan Khiew; Sian, Kong Tan; Alan, Fong; Tiong, Kiam Ong (BioMed Central Ltd., 2015)
Acute Inferior ST Elevation Myocardial Infarction (Ac-Inf-STEMI) and associated posterior and right ventricular (RV) infarction has been extensively studied with electrophysiology and echocardiography. A recent CMR study showed that poor RV function was associated with poor long term survival post myocardial infarction. However, limited CMR data exists especially on short term clinical outcomes in Ac-Inf-STEMI.